ABOUT THE UNIVERSITY AUTONOMY - Fumero Vargas, Patricia (2013)
This article studies the substantive principles of university autonomy and the changes in the concept from the Manifiesto Liminar to the contemporary understanding of autonomy, which is based on two types: procedural autonomy and substantive autonomy. It also discusses the role of authorities, professors and students, and the pressures of the State and society and their demand for accountability and transparency in the management of resources allocated to higher education.